2011
DOI: 10.1097/brs.0b013e3181db998c
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Unilateral and Bilateral Laminotomies for Decompression of L4–L5 Spinal Stenosis

Abstract: Both unilateral and bilateral laminotomies provide sufficient decompression of spinal stenosis and excellent pain reduction. However, unilateral laminotomy can be performed with shorter operative times and less blood loss. Radiologically, the use of a unilateral laminotomy induces less translational motion increase after surgery; thus, it may reduce the risk of late instability when compared with a bilateral laminotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 19 publications
7
57
0
2
Order By: Relevance
“…The postoperative CT scans demonstrated sufficient decompression with no residual stenosis. Mean preoperative measurement of dural sac diameter on MRI in millimeters was 63.3±19.6 compared to 181.3±35.5 post-operatively with mean improvement of 118 which mirror results obtained by Hong et al, 19 Nonetheless, no statistical relationship between decompression magnitude and clinical outcome. 36 The minimally invasive nature of MEDL for LCS goes hand in hand with lower EBL (estimated blood loss), and shorter days of hospitalization compared to open laminectomy.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The postoperative CT scans demonstrated sufficient decompression with no residual stenosis. Mean preoperative measurement of dural sac diameter on MRI in millimeters was 63.3±19.6 compared to 181.3±35.5 post-operatively with mean improvement of 118 which mirror results obtained by Hong et al, 19 Nonetheless, no statistical relationship between decompression magnitude and clinical outcome. 36 The minimally invasive nature of MEDL for LCS goes hand in hand with lower EBL (estimated blood loss), and shorter days of hospitalization compared to open laminectomy.…”
supporting
confidence: 71%
“…Clinical and Functional outcomes were analyzed utilizing Visual analogue scale for back and leg pain (VAS score from 0 to 10 where 0 indicate no pain and 10 points out the worst possible pain) as well as Japanese Orthopedic Association (JOA) score (maximum 29 points) 19 for low back pain. Both measures were applied pre-procedural and 3 months post-operative.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 In this study, the VAS was used to measure pain intensity. Patients were asked to rate their current level of pain ranging from 0 to 10 with 0 indicating no pain and 10 indicating the worst pain they can imagine.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Celik et al [10] observed an increased spinal instability after total laminectomy, leading to a bilateral microdecompressive approach to reduce this problem. Hong et al confuted this fact in their study [11], showing that bilateral decompression also increases the translational stress, thereby increasing the acquired listhesis. In their opinion, a unilateral decompression might reduce the risk of late instability.…”
Section: Radiological Outcomementioning
confidence: 90%
“…In particular, mechanical overload, devascularisation and decortication of the pars interarticularis seem to be important factors in developing a spondylolisthesis after spinal fusion [4,5]. In decompressive surgery, extensive bony resection can lead to post-operative lumbar instability and thus to spondylolisthesis [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%